Recente descoperiri paleolitice în sud-estul Transilvaniei: microzona Rupea – Homorod – Ungra, judeţul Braşov - Doboș, A.; Gridan, S. (Materiale și Cercetări Arheologice, 2018)
Our paper presents newly discovered Palaeolithic site(s) near the city of Rupea (Brașov County). The lithic pieces were found in the ploughed fields. The assemblage mainly features massive flakes knapped in siliceous sandstone. Among the retouched tools, the most numerous are the sidescrapers ; we also identified a Levallois core and two Levallois flakes. We suggest that the lithic inventory belongs to the Middle Palaeolithic